Key to Adults of North American Genera of the Subfamily Cecidomyiinae (Diptera: Cecidomyiidae) - Gagné, Raymond J. (Zootaxa, 2018)
Keys to the subfamilies of Cecidomyiidae and to the 150 genera of Cecidomyiinae known to occur in North America are presented. Information is given within the key for each of the genera on distribution, number of species and habits. Patterns of general distribution for the subfamily are discussed. A glossary to anatomical terms is included.